0
$\begingroup$

If $$A = \begin{bmatrix} 2 & 4 \\ 1 & 1 \\ \end{bmatrix}, $$ then use the Cayley-Hamilton Theorem to find $A^{-3}$.

This is how far I have gotten: \begin{align} p(\lambda) &= \lambda^2 -3\lambda -2 \\ p(A) &= 0 = A^2-3A-2I \\ A^2 &= 3A + 2I \\ A^3 &= 3A^2 + 2A = 11A+6I \end{align}

How do I proceed from here?

$\endgroup$
1
$\begingroup$

The characteristic polynomial is $(2-\lambda)(1-\lambda)-4=2-\lambda -2\lambda +\lambda^2 -4=\lambda^2-3\lambda -2$.

CH ensures you that $$ A^2 - 3A = +2I $$ hence $$ A(A-3I)=2I \qquad (A-3I)A = 2I $$ so that $A^{-1}=\frac{1}{2}(A-3I)$. From the equation above we also have, as you found, $$ A^3 = 3A^2 +2A = 3(3A+2I) + 2A= 11A+6I. $$ All in all, $$ A^{-3} = (A^{-1})^3 = \frac{1}{8}(A-3I)^3 = 8^{-1}(A^3 - 9A^2 + 27A - 27I) $$ which can be further simplified into $$ = 8^{-1}(11A+6I - 9(3A+2I)+27A-27I) = $$ $$ = \frac{1}{8}(11A+6I-27A -18 I +27A - 27I) = \frac{1}{8}(11A -39I) $$ thus $$ \boxed{A^{-3} = \frac{1}{8}\begin{bmatrix} -17 & 44 \\ 11 & -28 \end{bmatrix}}. $$

$\endgroup$
  • $\begingroup$ @Rócherz Gosh what a shame :-) $\endgroup$ – Romeo Mar 3 at 10:19
  • $\begingroup$ thanks for the detailed explanation! $\endgroup$ – DubsVeer23 Mar 3 at 11:15
  • $\begingroup$ You are welcome, I am glad if you found it helpful. $\endgroup$ – Romeo Mar 3 at 11:41
1
$\begingroup$

The Cayley-Hamilton theorem tells you that $A^2-3A-2I=0$; multiply by $A^{-1}$ to find $$ 2A^{-1}=A-3I $$ Multiply again by $2A^{-1}$: $$ 4A^{-2}=2I-6A^{-1}=2I-3(A-3I)=11I-3A $$ Multiply again by $2A^{-1}$: $$ 8A^{-3}=22A^{-1}-6I=11(A-3I)-6I=11A-39I $$ In a different way, you know from CH that $A^{-3}=\alpha A+\beta I$; then $$ I=\alpha A^4+\beta A^3 $$ and you can use CH for reducing the expression on the right.

$\endgroup$
1
$\begingroup$

Now go the other way around: \begin{align} p(\lambda) &= \lambda^2 -3\lambda -2 \\ p(A) &= O = A^2-3A-2I \\ I &= A \color{blue}{A^{-1}} = \tfrac12A^2 -\tfrac32 A = A \color{blue}{(\tfrac12 A -\tfrac32 I)} \\ A^{-1} &= \tfrac12 A -\tfrac32 I \end{align} Then $A^{-3}$ is just $A^{-1}$ times $A^{-1}$ times $A^{-1}$. You can reduce powers of $A$ using $p(A)$ if needed.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.